Assessment of Liver Function among Patients with Rheumatoid Arthritis Versus Patients with Psoriatic Arthritis Treated by Methotrexate - Nozad Adham , Berevan; Kader Media , Shwan (Diyala Journal of Medicine, 2022)
Background:Hepatotoxicity is a well-known adverse effect of methotrexate therapy. Objective: To assess liver functions such as ALT and AST in patients with rheumatoid arthritis and psoriatic arthritis receiving methotrexate and compare the liver functions in those patients cured by using methotrexate. Patients and Methods: This observational, cross-sectional analysis involved 50 patients with RA who satisfied EULAR-ACR-2010 standards for RA and 50 PSA cases who fulfilled CASPAR classification criteria for PSA, receiving constant weekly MTX therapy (oral or parenteral) up to 25mg, together with folic acid, liver function parameters such as ALT and AST in patients with rheumatoid and psoriatic arthritis were estimated and compared. Results: 78% of the 100 participants who were enrolled in this study were females. 10% of the participants were smokers, but there was no significant difference between the two groups (p = 0.410). None of the patients were alcoholics. There was a significant difference between the groups regarding the type of medications. 42% of the RA group were on other medications compared with 2% of the PSA cases (p < 0.001). The mean ALT of the PSA group (26.0 IU/L) was considerably (p = 0.005) greater than the mean of the RA group (19.6 IU/L) which shows an insignificant (p = 0.055) change between the two groups regarding the means of AST (26.3 IU/L in the PSA participants matched with 20.6 IU/L in the RA participants). Conclusion: Our research data shows that patients with PSA treated by methotrexate had a higher mean ALT level when compared with RA patients.